Pediatric Corneal Transplant Surgery: Challenges for Successful Outcome - Sharma, Ashok; Sharma, Rajan (Nepalese Journal of Ophthalmology, 2019)
Visual rehabilitation of pediatric corneal blinds is a major challenge to corneal transplant surgeons. Penetrating keratoplasty (PKP) is the only way to restore vision and prevent irreversible blindness due to amblyopia in children. Performing penetrating corneal grafts in children poses difficulty in evaluation, technical difficulties during surgery and problems during follow-up. Younger children do not cooperate for proper slit-lamp examination and need to be examined under general anaesthesia. In addition, the complications encountered post PKP, including allograft rejection, post PKP astigmatism and post PKP glaucoma are more frequent in pediatric group as compared to adult recipients. Even after a successful graft, the child requires rigorous treatment for amblyopia. Parents need to be counselled before surgery and possible visual outcome and chances of obtaining clear graft should be discussed.